PENGARUH KUALITAS PRODUK, PROMOSI, DAN KUALITAS PELAYANAN TERHADAP MINAT BELI MOTOR YAMAHA NMAX DI WILAYAH KOTA BEKASI - Handi Abdul Hadi; Dienni Ruhjatini Sholihah (Veteran Economics, Management, & Accounting Review, 2023)
The automotive industry is trying to rise from adversity after the pandemic, one of which is Yamaha, a motorcycle manufacturer from Japan, which is currently competing with its competitors. The purpose of this research is to analyze, find out and prove the influence of product quality, region, and service quality on interest in buying Yamaha Nmax in Bekasi City. The type of data used is quantitative data with a population of working age (17-64 years) Bekasi City. With a sample of 96 respondents and using purposive sampling method. The analytical technique used is Partial Least Square (PLS). The results obtained are the product quality, promotion, and service quality variables have a significant and significant effect on consumer buying interest. Keywords: Product Quality; Promotion; Service Quality; Buying Interest